Market quality and structural changes in the trading system: The case of X-Stream on the Colombian stock exchange. (2014)
We study the effect of X-Stream, the new trading platform of the Colombian Stock Exchange since February 2009, on the quality of the stock market. Contributing to the literature on market quality, this paper provides novel evidence of the effect of reforms on market design, trading rules and operational capabilities on a small and low liquidity emerging stock market. Starting from a proprietary database of transactional and order data from BVC, we use several econometric models to measure the effect of the new platform on daily and intraday volatility, liquidity (proportional bid-ask spread and price impact), and trading activity. The evidence suggests that X-Stream improved the liquidity and reduced the volatility of the overall market, especially of the most liquid stocks. These results support the investment on more sophisticated trading systems in Emerging Markets.